2014
DOI: 10.1111/1467-9817.12038
|View full text |Cite
|
Sign up to set email alerts
|

Is syllable segmentation developmentally constrained by consonant sonority within syllable boundaries in silent reading? Evidence in French children

Abstract: There is agreement that French typically reading children use syllable-sized units to segment words. Although the statistical properties of the initial syllables or the clusters within syllable boundaries seem to be crucial for syllable segmentation, little is known about the role of consonant sonority in silent reading. In two experiments that used audio-visual and visual pseudoword recognition tasks with 300 French typically developing children, we showed a progressive increase in the use of syllable segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Given that sensitivity to sonority-based constraints might be available at an early age and independently of linguistic experience and that it might also contribute to language acquisition (e.g., Gómez et al, 2014), current studies should examine how and when phonological sonority-based markedness impacts reading. Our prediction is that French children might refer to non-statistical properties when implementing syllable location and segmentation strategies in silent reading by taking advantage of their sensitivity to sonority-based constraints (e.g., Fabre and Bedoin, 2003;Maïonchi-Pino et al, 2012a,b, 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that sensitivity to sonority-based constraints might be available at an early age and independently of linguistic experience and that it might also contribute to language acquisition (e.g., Gómez et al, 2014), current studies should examine how and when phonological sonority-based markedness impacts reading. Our prediction is that French children might refer to non-statistical properties when implementing syllable location and segmentation strategies in silent reading by taking advantage of their sensitivity to sonority-based constraints (e.g., Fabre and Bedoin, 2003;Maïonchi-Pino et al, 2012a,b, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence regarding sonority in reading-related French studies remains scarce (but see Sprenger-Charolles and Siegel, 1997;Marouby-Terriou and Denhière, 2002;Maïonchi-Pino et al, 2012a,b, 2015. For instance, studies of reading aloud in preliterate and literate French children found that these children often reduced complex CVC or CCV syllable structures into simple CV syllables, thus indicating a preference to maximize sonority distance and eliminate sonorant consonants (e.g., "tru" → "tu"; "bar" → "ba"; e.g., Sprenger-Charolles and Siegel, 1997;Bastien-Toniazzo et al, 1999;Gnanadesikan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This a priori focus on an “all is a matter of statistical properties” could not be the sole and unique approach to account for these syllable-based effects. Questions come from controversies—and inconsistencies—in studies that banked on quantifiable orthographic statistical—and distributional—properties, like the bigram trough ( Seidenberg, 1987 ), either in children (e.g., in French, Kandel et al, 2011 ; Doignon-Camus et al, 2013 ; Doignon-Camus and Zagar, 2014 ; Maïonchi-Pino et al, 2015a ) or in adults (e.g., in French, Doignon and Zagar, 2005 , 2006 ; Doignon-Camus et al, 2009b ; in Spanish, Carreiras et al, 1993 ; Conrad et al, 2009 ; in English, Rapp, 1992 ; Muncer et al, 2014 ). The clincher of the bigram trough hypothesis to account for mapping letter clusters that frequently co-occur onto syllables and define perceptual syllable boundaries (i.e., “AN.VIL”; e.g., Seidenberg, 1987 ; Doignon-Camus et al, 2009a , b , 2013 ) is that letter co-occurrences straddling syllable boundaries (e.g., the bigram “NV” in “ANVIL”) are of lower frequency than letter co-occurrences preceding or after syllable boundaries (i.e., “AN” and “VI”).…”
Section: Introductionmentioning
confidence: 99%
“…One of the phonological universals—here sonority , which underlies the markedness constraints—has been demonstrated to crucially contribute to syllable-based effects in visual (pseudo)word processing in adults, children who are learning to read, and children with developmental dyslexia in French (e.g., Bedoin and Dissard, 2002 ; Marouby-Terriou and Denhière, 2002 ; Fabre and Bedoin, 2003 ; Maïonchi-Pino et al, 2012a , b , 2015a ; Maïonchi-Pino et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation